Implementation and maintenance of ISO 9001 : a case study in a Malaysian training academy - Victor, Azhar Thevaraj (2017)
The purpose of this study is to describe the Implementation and Maintenance of the ISO 9001 Quality Management standard in a Malaysian Training Academy. Though it has worldwide popularity, studies on the Implementation and Maintenance of the standard in Education is limited. This is more so in terms of its application in Training where there appears to be a paucity of studies on the subject. Further, the apparent lack of or nil studies in Malaysia on the subject accentuates the problem. The research design is qualitative and uses a descriptive single case study strategy in addressing the problem. Data collection and analysis was based on three sources of data which were: interviews; participant observations; and documents. Semistructured questions were used as the research instrument for online interviews. Purposive non-random sampling was used to select 8 key resource persons as respondents. The interview data were coded and analysed through thematic analysis. Structured and unstructured methods were used to capture participant observations. Document content analysis was employed for analysing documents and data from the 3 sources was triangulated. The findings were related to improvements made, benefits, critical success factors, problems faced and lessons learned. Generally, better documentation was ranked as the number one improvement arising from Implementation and Maintenance of the standard. Among other benefits of Implementation and Maintenance were better administrative efficiency and improved processes. It was also found that collective team effort made up of staff and management as well as effective communication played a key role in Implementation and Maintenance. The level of management commitment was found to be high with manpower and financial resource being adequate for the Implementation and Maintenance of the standard. Of note is the finding that Implementation and Maintenance of the standard improved the quality of training and services in the Academy. Management commitment, knowledgeable leadership and involvement of all staff were found to be the top three critical success factors for Implementation and Maintenance. Problems faced were attributed to the people factor in terms of their appreciation of the standard and willingness to contribute. As for lessons learned, the importance of leadership was emphasised. Further, it was found that the availability of a dedicated team of staff, better awareness and more focus on improving processes would enable better Implementation and Maintenance. Overall, the findings of the research show that ISO 9001 can be effectively implemented and maintained in Training through: proper planning, teamwork; training; communication; management commitment; knowledgeable leadership; and continuous improvement. The findings also show that external consultants and incentives or rewards were not a factor in the successful Implementation and Maintenance of the standard in the Academy. One of the implications of this research is its contribution to knowledge in terms of understanding how ISO 9001 can be successfully Implemented and Maintained in Training.